The Policy of Russia towards Greeks in the Early 19th Century - Giza, Antoni (Balcanica Posnaniensia. Acta et studia, 1999)
The article analyzes the policy of the Russian Empire toward the Greeks in the first half of the nineteenth century, particularly in the context of national liberation struggles against the Ottoman Empire. The research problem concerns Russian-Greek relations and Russian political concepts regarding the Greek question and the weakening of Turkey. The aim of the study is to show the political, religious, and ideological foundations of Russian interest in Greece. The author employs a historical-political method, analyzing political memoranda, diplomatic documents, and the views of Russian political elites. The article demonstrates that Russian policy toward the Greeks was not uniform: some elites supported the creation of an independent Greek state, while others sought only to expand Russian influence within the Ottoman Empire. The article discusses the activity of the Hetairia, the role of the Phanariots, and the significance of the idea of the “Third Rome” in Russian policy. The author emphasizes that the Greek question was an important element of Russian political and religious expansion in the Balkans. The results of the analysis indicate that Russia perceived the Greeks both as Orthodox allies and as an instrument for pursuing its own geopolitical goals.